M-Thyroid Care Mobile App: Virtual Video Consultation Application for Thyroid Clinic - Noorulsadiqin Azbiya Yaacob; Ahmad Hanis Mohd Shabli; Noor Rafhati Adyani Abdullah (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The present study aims to enhance thyroid clinics by proposing solutions through collaboration between medical experts and researchers, thereby enhancing the quality of healthcare services. To minimize unnecessary in-person consultations, a doctor requested the development of an app to address non-critical physical consultation appointments. Design-based research is a robust methodology that combines theory-driven inquiry with real-world problem-solving to develop interventions or serve as the basis for the research being discussed. M-Thyroid Care is designed to provide a practical and cost-effective platform for online consultations, facilitating video calls between patients and doctors. By leveraging this technology, the app aims to enhance patient monitoring and optimize the efficiency of thyroid clinic consultations. Moreover, the integrated chat feature allows for real-time communication, fostering effective doctor-patient interaction even outside of scheduled appointments. Additionally, the app enables the sharing of files, videos, and images, empowering doctors to review diagnostic reports and relevant visual data remotely. This further streamlines the consultation process. By reducing the reliance on physical visits for non-critical cases, the app has the potential to enhance access to specialized care, decrease wait times, and optimize resource utilization in the clinic setting. The prototype has the potential to enhance patient care, as demonstrated by this proactive engagement with stakeholders.